Effect of Alpha 1-Adrnoceptor Antagonists on Postsynaptic Sensitivity in Substantia Gelatinosa Neurons From Lumbosacral Spinal Cord in Rats Using Slice Patch-Clamp Technique for mEPSC - Uta, Daisuke (Int Neurourol J, 2020)
PURPOSE: Alpha1-adrenoceptors participate in improving storage symptoms of male lower urinary tract symptoms (LUTS). However, the mechanism of action of these compounds remains unclear. To clarify the mechanism of the α1-adrenoceptor antagonists, the amplitude of miniature excitatory postsynaptic currents (mEPSCs) was analyzed in the lumbosacral spinal cord in rats. METHODS: Male adult Sprague-Dawley rats were used. Blind whole-cell patch-clamp recordings were performed on substantia gelatinosa (SG) neurons in spinal cord slice preparations. The amplitude of mEPSCs was recorded in individual SG neurons to which α1-adrenoceptors (100μM naftopidil, 100μM tamsulosin, and 30μM silodosin) were applied sequentially with intervening washout periods. Individual amplitudes were analyzed. RESULTS: Pearson correlation coefficients (r) for the amplitudes of mEPSCs between the baseline and postadministration of α1-adrenoceptor antagonists indicated changes of the amplitude ranked in the order of naftopidil (r =0.393), tamsulosin (r=0.738), and silodosin (r=0.944). Together, the α1-adrenoceptor antagonists yielded significant increases in the amplitude of mEPSCs in SG neurons (n=108, P=0.012). However, the effects of each α1-adrenoceptor antagonist on the amplitude were as follows (relative to the baseline; n=36 each): naftopidil, P=0.129; tamsulosin, P=0.201; and silodosin, P=0.005. The rate of response to naftopidil for the outward current was relatively high among the α1-adrenoceptor blockers. An inward current was observed only with the naftopidil application. CONCLUSIONS: Alpha1-adrenoceptor antagonists changed the amplitudes of mEPSCs in a subset of SG neurons in slices prepared from the L6–S1 levels of rat spine. Although the α1-adrenoceptor antagonists generated inward or outward currents in the SG neurons, different rates of response were observed with each antagonist. These results are important for understanding the mechanisms of action (at the spinal level) of α1-adrenoceptor antagonists for the storage symptoms of male LUTS.